2014
DOI: 10.1007/s12288-014-0483-0
|View full text |Cite
|
Sign up to set email alerts
|

Prognostification of ALL by Cytogenetics

Abstract: Cytogenetic abnormalities in chromosomal number and structure are common in pediatric ALL and some have prognostic significance. One interesting association between cytogenetic status and treatment response involves the metabolism of methotrexate. Hyperdiploid lymphoblasts accumulate increased amounts of MTX and MTX polyglutamates, and they have higher basal apoptotic rates compared with leukemic cells with lower ploidy and normal cells. These characteristics may contribute to the better outcomes observed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 99 publications
0
21
0
Order By: Relevance
“…A number of recurrent chromosomal abnormalities have been shown to have prognostic significance in B‐ALL . Identification of prognostic factors is important for stratifying B‐ALL patients into risk groups and tailoring treatment accordingly .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of recurrent chromosomal abnormalities have been shown to have prognostic significance in B‐ALL . Identification of prognostic factors is important for stratifying B‐ALL patients into risk groups and tailoring treatment accordingly .…”
Section: Discussionmentioning
confidence: 99%
“…As in most hematological malignancies, cytogenetic aberrations are recognized to be an important determinant of the biological and clinical features in acute lymphoblastic leukemia (ALL) . In the classification scheme proposed by the World Health Organization (WHO), certain reciprocal chromosomal translocations, namely t(12;21)(p13;q22), t(9;22)(q34;q11), and translocations involving the 11q23 region, t(1;19)(q23;p13), and t(5;14)(q31;q32), are considered sufficient criteria for the definition of distinct disease entities .…”
Section: Introductionmentioning
confidence: 99%
“…For example, high hyperdiploidy is associated with improved relapse-free and overall survival, while complex karyotypes, low hypodiploidy and near haploidy are considered adverse prognostic factors 5 6. Some studies have shown that hyperdiploid lymphoblasts accumulate increased amounts of methotrexate and have a higher basal apoptotic rate, which could contribute to the improved outcomes of these patients 7. Cytogenetic analysis impacts treatment choice, with chromosomal abnormalities and their resultant molecular gene products now being used as targets for therapy 8…”
Section: Discussionmentioning
confidence: 99%
“…RUNX1, previously known as AML1, located at chromosome 21q22, encodes a transcription factor protein that is important for embryonic hematopoiesis as well as B-cell differentiation in adult blood cell progenitors. Chromosomal translocation t(12;21)(p13;q22) leads to the ETV6-RUNX1 fusion protein, consisting of the N-terminal non-DNA-binding domain of ETV6 combined with RUNX1, and is the most common alteration in childhood B-ALL (∼30%), but it is rarely observed in T-ALL (69). Children with B-ALL correlated with ETV6-RUNX1 show a highly good response to treatment (31).…”
Section: Translocations/rearrangementsmentioning
confidence: 99%